1995
DOI: 10.1084/jem.181.3.985
|View full text |Cite
|
Sign up to set email alerts
|

Role of 4-1BB ligand in costimulation of T lymphocyte growth and its upregulation on M12 B lymphomas by cAMP.

Abstract: SlltninlaryK46J B lymphomas express a T cell costimulatory activity that is not inhibited by CTLA-4Ig, anti-B7-1, anti-B7-2, anti-intercellular adhesion molecule 1 or antibodies to heat stable antigen. In this paper we report that this costimulatory activity is mediated at least in part by 4-1BB ligand, a member of the tumor necrosis factor (TNF) gene family that binds to 4-1BB, a T cell activation antigen with homology to the TNF/nerve growth factor receptor family. A fusion protein between 4-1BB and alkaline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
118
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(125 citation statements)
references
References 36 publications
5
118
0
2
Order By: Relevance
“…Studies by Cong et al (22) showed that the ability of native CT to selectively enhance B7-2 on macrophage was closely mimicked by dibutyryl cAMP, while the recombinant B subunit of CT had no effect on B7 expression. Moreover, it has been shown that cAMP can enhance B7 expression on B cells (32). While it is believed that the ADP-ribosyltransferase activity of LT does exert an effect on B7 expression, it has also been reported that a nonenzymatic mutant of LT can up-regulate B7-1 on macrophage (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Cong et al (22) showed that the ability of native CT to selectively enhance B7-2 on macrophage was closely mimicked by dibutyryl cAMP, while the recombinant B subunit of CT had no effect on B7 expression. Moreover, it has been shown that cAMP can enhance B7 expression on B cells (32). While it is believed that the ADP-ribosyltransferase activity of LT does exert an effect on B7 expression, it has also been reported that a nonenzymatic mutant of LT can up-regulate B7-1 on macrophage (11).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies using LT as adjuvant demonstrated that LT does retain a partial ability to enhance CD4 ϩ T cell responses to a coadministered Ag in B7-deficient mice (our unpublished observations), which is likely dependent upon the ability of native LT to enhance cAMP levels. Previous studies have shown that cAMP can affect a variety of costimulatory pathways that may partially overcome the need for B7 costimulation of CD4 ϩ T cells (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…4-1BB binds to a 4-1BB ligand (4-1BBL) expressed by activated antigen-presenting cells (APCs), including monocytes, macrophages, and B cells (Alderson et al, 1994;DeBenedette et al, 1995;Langstein et al, 1998;Pollok et al, 1994). The 4-1BB/4-1BBL interaction provides a costimulatory signal leading to proliferation and differentiation, as well as protection from activation-induced cell death of T cells Kwon et al, 2000;Saoulli et al, 1998;Takahashi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Its ligand, 4-1BBL, is expressed on activated APC [8][9][10][11][12]. Extensive evidence supports the role of 4-1BB as a costimulatory molecule that can function independently of CD28 [9,13,14] to activate T cells [10,15,16]. 4-1BB can influence cytokine production, proliferation and survival of T cells in vitro and in vivo [8][9][10][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Stimulatory anti-4-1BB antibodies show a preferential role for 4-1BB in CD8 + T cell activation in vitro [20]. However, purified CD4 T cells as well as antigen-specific MHC class II-restricted TCR transgenic cells can clearly respond to 4-1BBL in vitro [15,17,22,25].…”
Section: Introductionmentioning
confidence: 99%